Comparative Inhibition of Garlic as Natural-Antiseptic and Iodine as Synthetic-Antiseptic against Bacillus subtilis - Sazali, Munawir (Proceeding International Conference on Global Resource Conservation, 2013)
Iodine is an antiseptic that often utilized in various antiseptic synthetic trademark types. Nature substance garlic that contains alicin and scordinin are degradation character of membrane cells bacteria. Both of this antiseptics types done research to look at zero zone by Fledged Random Design with three treatment and six repetitions to get data analysis resistive extent each antiseptic into pure breeding Bacillus subtilis. Research method has done with observation, then using analysis ANOVA with analysiss result on checkmates significant 5% and keep on by advanced tests. Result advanced tests points out there is compare zoom that significant of nature and synthetic material, garlic has greater zero zone if compared to Iodine II. Clear zone average of garlic is 6.7 cm and Iodine as big as 3.0 cm. Of this research, result that garlic (Allium sativum) as nature antiseptic could utilize to prevent its happening infection effect of microbe.Keywords: antiseptic, Bacillus subtilis, garlic, Iodine